The progression of interface dermatitis by longitudinal examination of the histopathological features of at three-time intervals histopathology techniques in Fitzpatrick skin types III ? VI - Williams, Gavin (Department of Pathology, 2024)
Interface dermatoses (ID) are characterized by lymphocyte infiltration of the dermo-epidermal junction. The spectrum of ID includes lichen planus, lupus erythematosus, fixed drug eruption and Stevens-Johnson syndrome. A major sequela of ID in pigmented skin is post-inflammatory hyperpigmentation (PIHP). The frequency and severity of PIHP varies amongst different ID for unclear reasons. PIHP can be disfiguring following many dermatoses and some cosmetic and medical interventions, especially in dark-skinned individuals. There is limited understanding of PIHP pathomechanisms and little progress has been made in prevention and treatment of PIHP. ID provide a platform to understanding PIHP, a condition that predominantly affects darker skin. In this study we aimed to determine the progression of PIHP by longitudinal examination of the histopathological features of interface dermatitis at three-time intervals (acute stage, during resolution and upon complete healing) using electron microscopy and light microscopy. This was a prospective study undertaken at the Groote Schuur dermatology clinic over a 16-month period (March 2021 – June 2022). The study population included all patients with interface dermatitis that were diagnosed by the attending dermatologist and confirmed on biopsy during March to December 2021 and subsequently followed up for 6 months. Biopsies were taken at three-time intervals and compared morphologically by using transmission electron microscopy and light microscopy. In this study, it was noted that the degree of melanophages present in the majority of the participants correlate with the degree of Chronic inflammatory cell (CIC) infiltration. The only 2 factors that are common amongst all the patients across all the periods were the presence of CIC infiltrate and melanophages. Fixed drug eruption and bullous fixed drug eruption (BFDE) were assessed, and the key difference was the presence of full thickness epidermal necrosis due to the necrotic keratinocytes in the epidermal layer of BFDE. Upon assessing HMB45 and Melan-A staining, it was found that in participants with atrophic epidermal features, the HMB45 and Melan-A staining count was decreased or absent. This was also observed in participants with a necrotic epidermal layer and participants with discoid lupus erythematosus, however with regeneration improvement in the HMB45 and Melan-A staining results were observed. No correlation was found between the quantity of melanophages and extracellular melanin when assessing CD68 and MF stain results. CIC infiltrate and melanophages persisted in all participants from initial to final biopsy. All data showed no statistical significance, a larger population size could be used to further assess any significance in correlation seen.